2014
DOI: 10.1038/bjc.2014.510
|View full text |Cite
|
Sign up to set email alerts
|

Vaginal self-sampling is a cost-effective way to increase participation in a cervical cancer screening programme: a randomised trial

Abstract: Background:Cervical cancer screening coverage remains insufficient in most countries. Our objective was to assess whether in-home vaginal self-sampling with a dry swab for high-risk human papillomavirus (HR-HPV) testing is effective and cost-effective in increasing participation in cervical cancer screening.Methods:In March 2012, 6000 unscreened women aged 30–65 years, living in a French region covered by a screening programme, who had not responded to an initial invitation to have a Pap smear were equally ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
88
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(101 citation statements)
references
References 38 publications
13
88
0
Order By: Relevance
“…5 Furthermore, self-sampling has the potential of reducing cost when used at home with a return-mail kit. 27 …”
Section: Discussionmentioning
confidence: 99%
“…5 Furthermore, self-sampling has the potential of reducing cost when used at home with a return-mail kit. 27 …”
Section: Discussionmentioning
confidence: 99%
“…17 A recent study found that an in-home return mail kit sent to women aged 30-65 who had not previously responded to a call to screening was significantly more effective than a recall letter in eliciting a response. 18 Uptake of follow-up cervical screening among the women with a positive HPV result was 91%. This suggests that posting kits to older women could reduce the risk for those who have not taken full advantage of the call-recall system or at least enable any cancer to be diagnosed at an earlier stage with the potential to increase healthy years of life expectancy.…”
Section: Case For Screening Older Women and Some Possible Solutionsmentioning
confidence: 99%
“…29 In other countries that lack such comprehensive screening programs, opportunistic approaches using HPV self-sampling have also led to increased rates of screening among hard-toreach populations. 30,31 In the United States, our team is currently finalizing a randomized study testing HPV self-sampling among minority women lacking adequate screening from community-based nonclinical settings. 32 However, given our experience in using this approach in community-based samples and proven success in other clinical settings in other countries, we hypothesized that HPV self-sampling may be a viable strategy for cervical cancer screening in clinical settings.…”
Section: Introductionmentioning
confidence: 99%